Temporal Changes in the Microbial Community of a PAH-Contaminated Soil during Bench-Top Bioremediation - Rose, Caroline Gayle (University of Ottawa (Canada), 2010)
Contamination of soils with PAHs, substances that can pose serious environmental and human health risks, is a serious problem. Removal of risk requires effective and sustainable methods to decrease or eliminate toxicological hazard. Bioremediation is a sustainable option that can be accomplished by a variety of means. However, due to the limitations of classical culturing methods, there is a paucity of information regarding the composition of soil microbial communities, and moreover, the identity of organisms involved in contaminant catabolism. Newer, molecular techniques directly examine metagenomic DNA or RNA, and provide opportunities to investigate the genetic constitution of soil samples without the need for culturing. 16S rRNA has proven to be a valuable tool in the identification of soil microbes due to its highly conserved nature throughout the bacterial kingdom, in addition to inclusion of variable regions that are unique to a particular organism, or closely related group of organisms. This study used analysis of 16S rRNA gene sequences to examine the temporal changes in the soil microbial community in a PAH-contaminated soil during bioremediation. These results were compared with previously observed temporal changes in the chemical composition of the same soil during bioremediation. Interplay between the temporal changes of soil microbial community and the temporal changes of the PAH concentration was observed. The PAH concentration decreased an average of 77% across all treatments and reactors. Soil micro-organisms whose growth during treatment corresponded with a decline in PAH concentration included several known PAH-degraders such as Achromobacter, Acidovorax, Pseudomonas, Rhodanobacter and Stenotrophomonas. The metagenomic approach employed in this study can be used to evaluate innovative bioremediation methods, and moreover, identify members of the microbial community that are critical for the catabolism of PAHs.
Keywords: Biology, Microbiology.